Ice water immersion does not activate diffuse noxious inhibitory controls of spinal reflexes in sedated or anaesthetised dogs (Canis familiaris): a pilot study - Hunt, J. R.; Knazovicky, D.; Harris, J.; Kelly, S.; Knowles, T. G.; Murrell, J. C.; Lascelles, B. D. X. (Frontiers in Pain Research, 2025)
IntroductionDiffuse noxious inhibitory controls (DNIC) may be impaired in human subjects with osteoarthritis (OA) pain. Spontaneously occurring OA in dogs is considered a valuable model of human OA; however, methodology for assessing DNIC in dogs has not been fully developed. The aim of this study was to develop a suitable DNIC protocol using ice water immersion, similar to protocols used in humans.ObjectiveThis study objective was to create an experimental protocol for inducing DNIC in sedated or anesthetized dogs, ensuring it has face validity for future assessments of DNIC in studies involving the spontaneous canine OA model. We hypothesized that inducing DNIC in healthy dogs would result in a reduced electromyographic (EMG) response to a specific nociceptive stimulus.MethodsElectromyographic (EMG) responses of the cranial tibial muscle to test electrical stimuli and interdigital skin temperature were recorded in seven healthy dogs before and during a 20-min duration conditioning ice water immersion of the distal forelimb. The protocol was repeated for each dog using three different states: sedation with acepromazine or alfaxalone or anaesthesia with alfaxalone.ResultsIce water immersion caused a decrease of interdigital skin temperature in dogs in all three groups with the nadir (4.9–13.6°C) at 10 min following immersion. Skin temperatures remained significantly higher (p = 0.018) in alfaxalone sedated compared to acepromazine sedated dogs and returned to baseline more quickly than in acepromazine sedated dogs. Magnitudes of EMG responses were significantly larger in acepromazine sedated dogs compared to alfaxalone treated dogs (p < 0.001). DNIC was not induced, as the EMG magnitude did not significantly change over time for either the early (p = 0.07) or late responses (p = 0.27), and no significant interactions were observed between time and anaesthetic state in relation to EMG magnitude.ConclusionOur data suggest that a cold conditioning stimulus failed to elicit DNIC. It is possible that the magnitude of the conditioning stimulus was not sufficient to recruit DNIC in dogs.